การวิเคราะห์สถานการณ์คุณภาพการปฏิบัติงานของผู้ปฏิบัติการพยาบาลขั้นสูง งานการพยาบาลผู้ป่วยอายุรศาสตร์ โรงพยาบาลมหาราชนครเชียงใหม่ - จิราภรณ์ ธรรมสรางกูร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this study was to describe Advanced Practice Nurse (APN) practice quality in the Medical Nursing Division of Maharaj Nakorn Chiang Mai Hospital. The sample of this study was purposively selected and included 2 nurse administrators, 8 head nurses or head of units, 15 APNs, 4 healthcare personnel who work with the APNs, 2 patients and documents related to the APNs practices. The conceptual framework of this study was the quality of health care developed by Donabedian (2003) which comprises of structure, process, and outcomes. The instrument used was the semi-structure guideline for interview and focus group discussion. Data were collected through document review, interviews, and focus group discussions and was analyzed by using descriptive statistics and content analysis. The results of the situational analysis of the quality practice of APNs were: 1. The analysis of the structure found that there was a policy system for APN practices but that the policy implementation varied depending on the head nurses’ assignment. The position and career advancement of APNs were not clear. In addition, the distribution of APNs in each nursing unit was not appropriate. The three models of APN practices in the Medical Nursing Division were the full time APNs, part time APNs, and private practice of APNs. Pay was not appropriate to their knowledge, abilities and workloads. Suggestions include: develop the operational plan for APNs for every medical disease; develop role, function and career advancement; set up guidelines for assignment; allocate time, and provide offices and facilities to support APNs practices. 2. The analysis of the process found that APNs provide care to their patients following 9 competencies that the Thailand Nursing Council developed. However, the opportunity to practice depends on the characteristics of patients that were their target population and the assignment received from head nurses. The suggestions to nurse administrator were that they should provide an opportunity for APNs to perform their competencies as full-time APNs, and should develop the understanding of an APN’s role and competencies among health care professionals. 3. The analysis of outcomes found that APN practices effect patient outcomes, provider outcomes, and organizational outcomes. However the guidelines for outcome evaluation was not explicit. Therefore, the nurse administrators should develop the guidelines to evaluate APNs practices. The findings of this situational study will provide baseline information to develop a plan for improving the quality of APN practices in the Medical Nursing Division of Maharaj Nakorn Chiang Mai Hospital.